2019
DOI: 10.1044/2018_pers-sig3-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Building a Successful Voice Telepractice Program

Abstract: Purpose: Telepractice offers prevention, assessment, treatment, and consultation at a distance. This article provides an overview of telepractice with specific considerations and examples related to voice across licensure requirements, state and federal laws, reimbursement, documentation, and telepractice methods. Conclusion: As technology continues to advance and as client demand for telepractice services increases, practitioners need to create successful telepractice programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 30 publications
0
13
0
22
Order By: Relevance
“…Además, se pueden combinar servicios en línea y presenciales. 8 Marco legal y desafios eticos La evaluaci on y la rehabilitaci on de la voz deben enfrentar varios desafios durante los tiempos de pandemia. Es un concenso señalar que antes de administrar terapia vocal, los clínicos deberían realizar una laringoscopía para conocer el diagn ostico médico o la evaluaci on funcional.…”
Section: Article In Pressunclassified
“…Además, se pueden combinar servicios en línea y presenciales. 8 Marco legal y desafios eticos La evaluaci on y la rehabilitaci on de la voz deben enfrentar varios desafios durante los tiempos de pandemia. Es un concenso señalar que antes de administrar terapia vocal, los clínicos deberían realizar una laringoscopía para conocer el diagn ostico médico o la evaluaci on funcional.…”
Section: Article In Pressunclassified
“…Além disso, é possível combinar atendimentos on-line e presenciais. 8 Questões jur ıdicas e desafios eticos A avaliação e tratamento vocal enfrentam vários desafios durante os tempos de pandemia. Há um consenso sobre a necessidade de o paciente ser submetido a uma avaliação laringosc opica para diagn ostico médico antes de início da terapia fonoaudiol ogica para a voz.…”
Section: Considerações Associadas Aos Procedimentos De Vozunclassified
“…Existem evidencias atuais confirmando que os clínicos possuem nível adequado de domínio tecnol ogico para ministrar sessões de terapia por teleatendimento. 8 Novas pesquisas são necessárias para identificar como estabelecer vínculo nesta modalidade de prestação de serviço. 82 Sobre o ambiente terapêutico para se ministrar uma sessão por teleatendimento, as seguintes sugestões devem ser consideradas: 83 As evidências demonstram claramente que quanto maior o tempo de intubação (superior a 48h), maior a prevalência e gravidade das lesões laríngeas p os-extubação.…”
Section: Preparando Uma Sessão De Teleatendimentounclassified
See 1 more Smart Citation
“…Overall, it is suggested that further measures be taken by scientific associations to eliminate barriers in the path of therapists and promote telepractice facilitators so that this type of care be used more extensively by SLPs. It should be noted that so far many associations, including ASHA, have emphasized on the use of telepractice by SLPs [ 40 , 42 ]. The ASHA have mentioned that telepractice is a viable process for delivering SLP services during COVID-19 pandemic and that both evaluation and treatment were possible through telepractice [ 40 ].…”
Section: Introductionmentioning
confidence: 99%